1989
DOI: 10.1111/j.1399-0039.1989.tb01674.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DR4 associated Dw types in rheumatoid arthritis

Abstract: Frequencies of HLA-DR4 and its related Dw types were compared between randomly selected normal controls and the index cases of multiplex rheumatoid arthritis (RA) families. A DR4 frequency of 68.3% was observed in index cases (n = 57) compared to 31.2% in normal controls (n = 96). Cellular typing with homozygous typing cells (HTCs) revealed significant increases of Dw4 (49.1% vs 22.9% RR = 3.2 p less than 0.001) and Dw14 (22.8% vs 2.1% RR = 13.9 p less than 0.001) in the index cases. A non-significant increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

1991
1991
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…This confirmed the previous cellular typing of these 2 extended haplotypes as Dw4 (Ollier et al, 1989) which corresponds toDRBl*O4OI. Also, all patients and controls who carried HLA-A2, B62 and DR4 were DR4 subtyped as having 0401.…”
Section: Hla-dr4 Subtypessupporting
confidence: 78%
See 3 more Smart Citations
“…This confirmed the previous cellular typing of these 2 extended haplotypes as Dw4 (Ollier et al, 1989) which corresponds toDRBl*O4OI. Also, all patients and controls who carried HLA-A2, B62 and DR4 were DR4 subtyped as having 0401.…”
Section: Hla-dr4 Subtypessupporting
confidence: 78%
“…In view of the increased risk of lymphoid but not myeloid malignancies in RA, it is interesting that CLL, but not CML, shares the same DR4 subtypic association with RA. Given the fact that the commonest ancestral DR4 haplotypes, B44DR4 and B62DR4, both carry DRBl*O401, the DR4 subtypic associations may be simply due to already known haplotypic associations in RA (Ollier et al, 1989;McCluskey et al, 1983;Fraser et aL, 1990) and leukaemia (Dorak et al, 1994~). Furthermore, the haplotype A2B62DR4 is associated with the adult-onset form of RA (Fraser et al, 1990) and the present study showed a strong association of the simultaneous occurrence of its alleles in an adult lymphoid malignancy.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In all four studies, no association appeared of any particular HLA-DQ allele with disease, either in adult (9,49,50) or juvenile (51) patients. Thus, the contribution of specifi c HLA-DQ alleles to RA appears to be minimal.…”
Section: Rheumatoid Arthritismentioning
confidence: 71%